Problematika dan Transformasi Penyesuaian Media Digital dalam Pembelajaran IPS SD (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to initiate the problems and transformations in the implementation of Social Sciences (IPS) subjects by utilizing digital media through the method of literature study or literature review. The research findings indicate that there are various significant problems, such as limited internet use in the school environment, inadequate access to digital media, the digital capability gap between educators and students, and minimal technical support and low quality digital resources. To overcome these challenges, this study proposes several solutions, including the development of learning technology innovations, increasing digital literacy and skills for teachers and students, and providing interactive, interesting, and easily accessible digital learning media. With these adaptations and solutions, it is hoped that IPS learning at the elementary school (SD) level can increase significantly in terms of effectiveness and efficiency, and be able to develop students' critical and analytical thinking skills. This finding is an important benchmark for the development of the world of education in the digital era, especially in the context of elementary school IPS learning.